RANCANG BANGUN APLIKASI ABSENSI MENGGUNAKAN LEARNING MANAGEMENT SYSTEM BERBASIS ANDROID - Thoha Nurhadiyan; Khoyzuroni AlFarukhi (Jurnal Ilmiah Sains dan Teknologi, 2019)
Vocational High School (Vocational) Bhakti Pertiwi Ciptayasa or BPC is a Private Vocational High School located in Ciruas District, Serang Regency, Banten. Same as in general the level of vocational high school, the learning process in Vocational High School Ciptayasa is taken in time 3 years, starting from class 10 to class 12. BPC has 2 masters, namely the AK class (Accounting) and TKJ class (Computer and Network Engineering). Problems that often occur namely. Student attendance and grades are input conventionally and not well organized so parents do not know that their child is attending school or not. Data processing in the Vocational School Bhakti Pertiwi Ciptayasa which is still conventional so that sometimes there is data that is lost or damaged. In this study the author uses the prototype method. As for data collection techniques using interviews, observation, and literature study. Based on the results of this research at the Bhakti Pertiwi Ciptaysa Senior High School by testing the blackbox system it can be concluded that the results of making this software are expected to make it easier to manage classes, especially for student absences and grades so that they can assist in the learning process